1994
DOI: 10.1210/jcem.78.1.8288720
|View full text |Cite
|
Sign up to set email alerts
|

In situ hybridization study of estrogen receptor messenger ribonucleic acid in human adenohypophysial cells and pituitary adenomas.

Abstract: Estrogen receptor (ER) was demonstrated in nontumorous and adenomatous human pituitaries by autoradiography and biochemical assays. In the present study, we investigated ER mRNA by in situ hybridization applied on paraffin section of 9 nontumorous pituitaries obtained at surgery or autopsy and 109 surgically removed adenomas. In nontumorous pituitaries, in situ hybridization combined with immunocytochemistry revealed hybridization signal in GH-, PRL-, ACTH-, TSH-, and LH/FSH-immunoreactive cells, with the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
30
0
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 26 publications
5
30
0
1
Order By: Relevance
“…Since it has been demonstrated that ERa is expressed in GH-positive cells in the pituitary (Stefaneanu et al 1994) and as radiolabeled estrogen was found in GH immunoreactive cells (Keefer et al 1976), we first determined the effect of E 2 B and 8-PN on pituitary GH secretion. Both the high dose of 8-PN and the high dose of E 2 B significantly upregulated GH levels.…”
Section: Discussionmentioning
confidence: 99%
“…Since it has been demonstrated that ERa is expressed in GH-positive cells in the pituitary (Stefaneanu et al 1994) and as radiolabeled estrogen was found in GH immunoreactive cells (Keefer et al 1976), we first determined the effect of E 2 B and 8-PN on pituitary GH secretion. Both the high dose of 8-PN and the high dose of E 2 B significantly upregulated GH levels.…”
Section: Discussionmentioning
confidence: 99%
“…Embora os homens tenham níveis de estrogênio mais baixos que as mulheres, maior expressão de receptor estrogênico tem sido demonstrada em prolactinomas de homens que nos de mulheres. Este pode ser um dos fatores responsáveis pela maior agressividade da doença no sexo masculino, independente da precocidade ou não do diagnóstico 30,31 .…”
Section: Discussionunclassified
“…We have documented reduced expression of isoforms of thyroid hormone receptors and retinoid X receptors in NFTs (Gittoes et al 1997a,b) compared with the findings in normal pituitaries. Absent, or reduced, expression of oestrogen receptor ( ) protein has also been demonstrated in NFTs (Nakao et al 1989, Friend et al 1994, Stefaneanu et al 1994, Zafar et al 1995, Gittoes et al 1997a. The latter observation is of particular relevance, as NFTs are believed to be derived from cells of the gonadotroph lineage and thus would be expected to express oestrogen receptor (Friend et al 1994, Zafar et al 1995.…”
Section: Abnormal Expression Of Nuclear Steroid/thyroid Hormone Recepmentioning
confidence: 99%